Birth Preparedness among Women Who Gave Birth in the Last Twelve Months in Jardega Jarte District, Western Ethiopia - Tiruneh Asrat; Negga Baraki; Nega Assefa; Getachew Alemkere (Journal of Pregnancy)
Background. Lack of preparedness for rapid action in the event of obstetric complications was the major problem contributing for delay in receiving skilled obstetric care. This study aimed to assess birth preparedness and factors associated with it among women who gave birth in the last 12 months preceding the survey in Jardega Jarte district, Western Ethiopia. Methods. A community-based cross-sectional study was conducted from January to February 2016. A total of 581 women who gave birth recently were randomly selected for an interview. Data were entered and analyzed using SPSS version 21. Binary logistic regression was performed to identify predictive factors. Statistical significance was declared at p<0.05. Results. From 581 questionnaires distributed, 570 were completed making the response rate 98%. The mean age was 28 with a standard deviation of 5 years. Ninety percent of the respondents were rural in residency. The average family size was 6 with a range of 13. Majority of the respondents were grand multipara, 261(45.6%). Despite the majority (69.3%) of the respondents reported as they made arrangement for birth, only 27.5% of them were well-prepared for birth and its complication management. Urban residency (AOR=3.4, 95% CI: 1.7-6.9), primipara (AOR=5.12, 95% CI: 2.4-10.8), history of obstetric complication (AOR=4.05, 95% CI: 2.4-7.75), and attending antenatal care (AOR=2.9, 95% CI: 1.67-5.16) were independently associated with preparation for birth and its complication. Conclusion. This study revealed that only about a quarter of pregnant women were well-prepared for delivery and complication management. Urban residencies, history of past obstetric complications, availing antenatal care, primipara, and absence of an under-five child in the household during recent delivery were predictors of birth preparedness. On the other hand, availing health service to such rural areas, giving more attention to the grand multiparous mothers with large family size will be important interventions to prevent pregnancy-related complications. Such efforts would benefit from accessing antenatal care and family planning services.